The effect of different concentration of composite coagulant on different arrangement of electrodes for hybrid composite coagulation and lector coagulation treatment of landfill leachate - Mohd Amdan, Nur Syahirah (2021)
The development and the population of the country cause the increment of solid waste generation. When the solid waste is increasing, leachate production also increases. The drawback is the potential of leachate to seep into the ground soil that able to contaminate the surrounding area. In this study, the combined treatment of electrocoagulation